Myeloid sarcoma of bile ducts presenting as obstructive jaundice - A case report - Ayushi Agarwal; Tina Dadu; V P Bhalla; Veena Malhotra (Wolters Kluwer Medknow Publications, 2019)
Myeloid sarcoma is an extra medullary manifestation of acute myeloid leukemia (AML). Primary involvement of the biliary tract with myeloid sarcoma presenting as obstructive jaundice without evidence of leukemia is very rare. Here we present a case of 72 year old lady, who initially presented with features of biliary obstruction and was clinically considered as cholangiocarcinoma. She was diagnosed as myeloid sarcoma involving right and left hepatic duct, common bile duct (CBD) on histopathological and immunohistochemistry (IHC) examination after surgical resection. Since she did not show evidence of leukemia on peripheral blood and bone marrow examination treatment was deferred. However, she developed full blown picture of AML within two months and succumbed to her disease. We conclude that obstructive jaundice can be the presenting symptom in myeloid sarcoma without evidence of AML in peripheral blood and bone marrow. However, these cases have to be treated aggressively to obtain remission.